Husk detection using thermal imaging technology - Jamil, Norazlida; Bejo, Siti Khairunniza (Elsevier, 2014)
Harvested paddy normally contains impurities including husk. This study focuses on the use of thermal imaging to detect husk. Heating and cooling treatment was applied to 20%, 40%, 60%, 100% husk and 100% seed to differentiate between husk and seeds due to heat transfer. From result, mean pixel of seed thermal image is higher compared to husks. It value at 25 s gave a suitable indicator to separate between seed and husk. The technique can be used to detect husk with 100% success rate for 20% and 40%, 98.33% for 60% and 97.67% for 100% husk, while 94.33% for 100% seeds.